Functional herbal food ingredients used in type 2 diabetes mellitus. Pharmacogansy Review 2012:6:37-45 - Perera, P. K.; Li, Y. (My University, 2012)
The patent herbal compound drug, Yi Shen Juan Bi (YJB), has been found to be effective for the treatment of rheumatoid arthritis (RA), and our previous studies revealed that it has potent anti rheumatic effects . We have conducted further investigations into the anti arthritic activity of YJB using macrophage and synoviocytes cells in an ex-vivo serum pharmacology assay. For that purpose, we used mouse serum containing YJB and analyzed the macrophage derived cytokine tumor necrosis factor alpha (TNF-á) and interleukin-1 (IL-1) using ELISA kits, nitric oxide (NO) by Griess reaction and the proliferation of rats synoviocytes stimulated by TNF-á by MTT reduction assay in vitro. In addition, we analyzed the cytotoxicity concentrations of YJB by MTT reduction assay. This study confirmed the anti-rheumatic effects of YJB correlated with a significant decrease of TNF-á, IL-1 and NO production by macrophages and also with significant decrease in the proliferation of synoviocytes in vitro. A subsequent cytotoxicity assay also revealed no significant difference in cell viability. Our results suggest that YJB is a potential anti-rheumatic agent targeting the inflammatory and immunomodulatory response of macrophages and synoviocyte cells.